PEDAGOGICAL CONDITIONS OF EDUCATION OF SPORTS MOTIVATION - Irmatov Shavkat Anvarovich; Shokirov Shuxrat G’ayratovich (Galaxy International Interdisciplinary Research Journal, 2024)
Based on the theoretical analysis of scientific and methodological literature, the essence and content of sports motivation and the features of its connection with the personal qualities of athletes are determined. Pedagogical conditions for the formation of sports motivation in volleyball players aged 15-16 are identified.